IMPLEMENTASI RESTORATIVE JUSTICE MELALUI DIVERSI DALAM SISTEM PERADILAN ANAK (Faculty of Law, University of Palembang, 2024)
Children are the nation's generation and have a strategic role in the sustainability of a nation's life inthe future. If a child comes into contact with the law, he or she is given the protection of the JuvenileCriminal Justice System Law which is mandated with the concept of implementing Restorative Justicethrough diversion in the juvenile justice system. The aim of this research is to find out how tostrengthen protection and advocacy, as well as implement Restorative Justice for children in conflictwith the law. The approach uses qualitative and normative methods, which are sourced from data andstatutory regulatory materials which are reviewed and analyzed descriptively. The conclusion of thisarticle is to see how weak regulations and handling are regarding the juvenile criminal justice systemand how far the implementation of Restorative Justice through diversion is applied in handlingjuvenile cases. It is hoped that the Juvenile Criminal Justice System Law will be friendlier to childrenin conflict with the law.